PRESUPPOSITION IN “THE WATER HORSE: LEGEND OF THE DEEP (2007)” MOVIE - Perdana, Yanuarius Rangga; Surya, Satyawati; Valiantien, Nita Maya (Fakultas Ilmu Budaya Universitas Mulawarman, 2022)
The aim of this research is to find out types of presupposition. Yule’s theory of types of presupposition is used by the researcher to find out and describe the types of presupposition found in “The Water Horse: Legend of the Deep (2007)” movie. The researcher uses descriptive qualitative method. The object of this research is a movie entitled “The Water Horse: Legend of the Deep (2007)” directed by Jay Russell. The data were taken from all scenes including the utterances uttered by speaker and heard by the interlocutors. The data source of this research is the movie script of “The Water Horse: Legend of the Deep (2007)”. In collecting data, the researcher chose the data which are all of the types of presupposition uttered by main characters in the movie. The researcher conducted observation by repeatedly watching, taking notes and classifying utterances for the type of presupposition uttered by the main characters in the movie. The researcher found 4 of 6 Yule’s six types of presupposition theory uttered by the characters in the movie. Those four types of presupposition are 46 utterances of existential presupposition which is the most frequently type uttered by the characters in this research, 11 utterances of structural presupposition, 9 utterances of lexical presupposition and the last least frequently type uttered by the characters is counter-factual presupposition which has 4 utterances only.